2022
DOI: 10.1039/d2nj03939g
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon supported Fe–Cu–NC as an efficient cathode catalyst for a microbial fuel cell

Abstract: Microbial fuel cell (MFC) is a promising device for converting bioenergy into electrical energy, but its performance is mainly limited by the slow kinetics of oxygen reduction reaction (ORR). Hence,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…[4][5][6] Pt and Pt-based catalysts are well known for their outstanding ORR activity, but their resource scarcity and prohibitive cost greatly limit their widespread commercial application. [7][8][9][10][11] Therefore, it is necessary to develop efficient synthesis and implementation methods for nonplatinum-group metal (non-PGM) materials as cathode catalysts in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Pt and Pt-based catalysts are well known for their outstanding ORR activity, but their resource scarcity and prohibitive cost greatly limit their widespread commercial application. [7][8][9][10][11] Therefore, it is necessary to develop efficient synthesis and implementation methods for nonplatinum-group metal (non-PGM) materials as cathode catalysts in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they also suffer from a lack of dual functions and poor stability. [17][18][19][20][21][22] Therefore, it is urgent to design and synthesize non-precious catalysts that are earth-abundant, cost-effective active, stable, and bifunctional.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works reported that the multi-atom sites exhibit enhanced ORR performance because of the atomic pair effects [21][22][23][24]. The paired atom sites such as Fe-Cu or Fe-Co would change the bonding energy of the active sites (Fe-N 4 sites for example) and bene tted the absorption/desorption of the intermediates [25]. However, the nanoclusters of metals on carbon-based materials are hard to be distinguished and characterized, which is because of the aggregation of the metal elements and the movement and the deformation of the electrocatalysts during the ORR process [26][27].…”
Section: Introductionmentioning
confidence: 99%